1999
DOI: 10.1207/s15327914nc340109
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Study of Stage III and IV Non-Small Cell Lung Cancer Patients Taking a Specific Dietary Supplement

Abstract: This phase I/II study evaluates the influence of selected vegetables (SV) that contain known antitumor components on the survival of stage III-IV non-small cell lung cancer (NSCLC) patients. All patients were treated with conventional therapies. SV was added to the daily diet of 5 stage I patients in the toxicity study group (TG) and 6 stage III and IV patients in the treatment group (SVG), but not to the diet of 13 stage III and IV patients in the control group (CG). Age, Karnofsky performance status (KPS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Two small studies sought to determine whether dietary intervention with selected vegetables improved survival among those with Stage III or IV non-small-cell lung cancer. 122,123 Weight loss was less and survival was longer in the intervention groups in those studies. Although these results are encouraging, these findings need to be confirmed by other investigators and in larger studies.…”
Section: Lung Cancermentioning
confidence: 88%
“…Two small studies sought to determine whether dietary intervention with selected vegetables improved survival among those with Stage III or IV non-small-cell lung cancer. 122,123 Weight loss was less and survival was longer in the intervention groups in those studies. Although these results are encouraging, these findings need to be confirmed by other investigators and in larger studies.…”
Section: Lung Cancermentioning
confidence: 88%
“…A dietary supplementation of vegetable soup preparation given in clinical trials with patients having stage III and IV non-small cell lung cancer was reported (20, 21). The diets, which contain vegetables and fruits with multiple functional components have no side-effects, and believed to be effective for prevention of cancer and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival of control patients was 4 months (mean 4.8 months), while that of patients who received the vegetable remedy was 15.5 months (mean 15 months). This non-toxic vegetable brew was also reported to improve quality of life [39].…”
mentioning
confidence: 95%